The effects of feeding corn containing an alpha-amylase gene on the performance and digestibility of growing cattle - Johnson, Marissa A. (Kansas State University, 2019)
Two growth performance studies and two digestibility trials were conducted to evaluate the effects of feeding Enogen feed Corn silage and corn grain to growing cattle. In Experiment 1, there were a total of four diets offered for ad libitum intake. The four diets consisted of two varieties of corn (Enogen Feed Corn (EFC) vs. negative isoline control corn (CON)) with two different methods of corn processing (dry-rolled corn (DRC) vs. whole-shelled corn (WC)) and were formulated to provide 1.13 Mcal NEg/kg DM. ADG and final BW tended to be greater for calves fed EFC (P < 0.10). Feed efficiency was greater for calves fed EFC (P < 0.01), improving by 5.50% over calves fed CON corn. In Experiment 2, a digestibility trial was conducted using 7 cannulated Holstein steers fed the same diets from Experiment 1. Ruminal pH was not affected by corn variety (P > 0.82). Liquid passage rate was greater for CON-fed calves, which resulted in decreased digestibility. Total tract organic matter (OM) and dry matter (DM) digestibility was greater for EFC-fed calves (P < 0.04). In Experiment 3, there were a total of four diets offered for ad libitum intake. Diets consisted of two varieties of corn silage (EFC vs. CON) and two varieties of DRC (EFC vs. CON) and were formulated to provide 1.11 Mcal NEg/kg DM. ADG was greater (P < 0.01) for calves fed EFC silage and feed efficiency tended to be greater for calves fed EFC silage (P < 0.14). Feed efficiency of calves receiving EFC silage improved by 3.30% and ADG improved by 6.00%. In Experiment 4, a digestibility trial was conducted using 8 cannulated beef steers fed the same diets from Experiment 3. Liquid passage rate (P > 0.20), ruminal pH (P > 0.23), and ruminal VFA concentrations (P > 0.35) were unaffected by treatment. Numerical differences showed a 2.5% and a 2.2% increase in total tract DM digestibility and total tract OM digestibility, respectively, for calves fed the EFC silage diets.
Keywords: Enogen Feed Corn; Alpha-amylase; Growing cattle; Corn silage; Dry-rolled corn